The Influence of Environmental Performance and Disclosure of Carbon Emissions on Firm Value (Study on Companies Listed on the BEI) - Fadhilah, Afifah Nurul; Puspita, Deta; Rachmani, Diah Ayu; Wiralestari, Wiralestari; Mukhzarudfa, Mukhzarudfa; Kusumastuti, Ratih; Putra, Wirmie Eka (Formosa Journal of Multidisciplinary Research, 2025)
The objective of this study is to investigate the influence of environmental performance and carbon emission disclosure on firm value. The population of this study encompasses mining companies listed on the Indonesia Stock Exchange during the 2018-2022 period. Samples were chosen using purposive sampling, resulting in 70 observation samples. The analysis technique employed in this study utilizes a panel data regression model, with the Random Effect Model (REM) selected as the research model. The findings of this study indicate that environmental performance does not exert a significant impact on firm value, while carbon emission disclosure exhibits a significant positive influence on firm value.